Innovation for Positive Sustainable Legacy From Mega Sports Events: Virtual Reality as a Tool for Social Inclusion Legacy for Paris 2024 Paralympic Games - Byers, Terri; Hayday, Emily Jane; Mason, Fred; Lunga, Phillip; Headley, Daneka (Frontiers in Sports and Active Living, 2021)
There is significant interest in how sports events and their associated legacies could act as a platform to address global challenges and engender social change. The UN has acknowledged the important role that sport plays in supporting the UN 2030 Agenda for Sustainable Development and the Olympic movement could be argued as central to that objective. Yet critical questions and concerns have been raised about the growing expenditure, viability, long term legacy and impacts of mega sports events, such as the Olympics Games. While much evidence has focused on the challenges of creating legacy for Olympic Games (Brittain, Bocarro, Byers & Swart, 2018), there is considerably less literature on understanding the Paralympic context. The purpose of this paper is to discuss the role of innovation in creating legacy from MSE and propose a theoretical and methodological plan for such research. Innovation, a key driver in organizational performance is suggested as essential to defining, planning for and measuring legacy. We specifically examine the potential of virtual reality (VR) as a technological innovation which can help create a social inclusion legacy in the context of Paris 2024 Olympic/Paralympic Games. Building on the conceptual model of Byers, Hayday & Pappous (2020), which identified legacy as a ‘wicked problem’, this paper discusses the importance of innovation with regards to legacy, by suggesting a new application for VR technology in the context of legacy related to social inclusion. Manzoor & Vimarlund (2018) have identified information technology as a valuable facilitator of social inclusion for individuals with a disability. We specifically examine the potential of VR as a technological innovation which can help create legacy through influencing unconscious biases (symbolic ableism) toward diversity such as disability, gender and race.